2000
DOI: 10.3171/jns.2000.92.6.0920
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Chiari Type I malformations identified on magnetic resonance imaging

Abstract: The authors suggest that the isolated finding of tonsillar herniation is of limited prognostic utility and must be considered in the context of all available clinical and radiographic data. Strategies for treating patients with asymptomatic CMIs are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
290
5
16

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(321 citation statements)
references
References 51 publications
(84 reference statements)
10
290
5
16
Order By: Relevance
“…This prevalence contrasts sharply with that reported by Meadows et al, who reviewed the brain and cervical-spine MRIs of 22,591 patients. They could identify only 175 patients in whom tonsillar ectopia exceeded 5 mm, i.e., a prevalence of 0.77% [36].…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence contrasts sharply with that reported by Meadows et al, who reviewed the brain and cervical-spine MRIs of 22,591 patients. They could identify only 175 patients in whom tonsillar ectopia exceeded 5 mm, i.e., a prevalence of 0.77% [36].…”
Section: Discussionmentioning
confidence: 99%
“…139,140,151 If the current imaging definition of tonsils 5 mm below the foramen magnum is used, CM is not rare. 78,[138][139][140]153,154 CM is found in approximately 0.8% to 1% of all patients undergoing MRI when age is not considered. 78,138,153 When prevalence is stratified by age, it is clear that the prevalence in children and young adults is greater.…”
Section: Chiari and Syringomyeliamentioning
confidence: 99%
“…78,[138][139][140]153,154 CM is found in approximately 0.8% to 1% of all patients undergoing MRI when age is not considered. 78,138,153 When prevalence is stratified by age, it is clear that the prevalence in children and young adults is greater. 152 As many as 3.6% of children undergoing MRI of the brain or cervical spine have CM by imaging criteria; most children who meet the definition of CM by imaging criteria are asymptomatic.…”
Section: Chiari and Syringomyeliamentioning
confidence: 99%
“…Based on studies, the incidence of ACM type I remains unclear [3]. However, retrospective investigation of magnetic resonance imaging (MRI) of the head revealed that the prevalence may be as high as 1 in 1280 [4].…”
Section: Introductionmentioning
confidence: 99%